AT1 AND GPER-1 HETERODIMERIZATION POTENTIATES CYP11B2 GENE EXPRESSION IN ALDOSTERONE PRODUCING ADENOMA. (June 2018) - Piazza, M.; Caroccia, B.; Seccia, T.M.; Pivato, L.; Rossi, G.P.
Abstract : Objective: Aldosterone producing adenomas (APAs) exhibit increased expression levels of G protein-coupled receptors (GPCRs), including the GPCRs Angiotensin (Ang) II type 1 receptor (AT1R) and G protein-coupled estrogen receptor-1 (GPER-1), which trigger aldosterone production by binding Ang II and 17B-estradiol or aldosterone. Since a functional crosstalk between GPCRs has been reported, we investigated if AT1R and GPER-1 crosstalk to activate CYP11B2 gene expression in APA Design and method: APA strips and adrenocortical carcinoma cell line HAC15 were exposed to [100 nM] aldosterone alone or in presence of [100 nM] Ang II for 12 hours, and/or after pre-treatment with the selective AT1R antagonist irbesartan and/or the selective GPER-1 antagonist G36. The experimental end-point was CYP11B2 gene expression change. HAC15 proteins were immunoprecipitated with an antibody for AT1R, and GPER-1 expression was revealed by immunoblot in immunoprecipitated proteins. Results: In APA strips both aldosterone and Ang II increased CYP11B2 gene expression (+220% and + 190%, respectively, p < 0.01 vs untreated); aldosterone on top of Ang II potentiated the secretagogue effect of Ang II (+400%, p < 0.001 vs untreated). The synergistic effect of aldosterone and Ang II was inhibited by either irbesartan or G36. Similarly, in HAC15 cells aldosterone potentiated the effect of Ang II (+800% vs Ang II alone; + 1300% vs aldosterone alone), and pre-treatment with irbesartan and/or G36 blunted the synergistic effect of aldosterone plus Ang II. After immunoprecipitation for AT1R, GPER-1 protein expression was detected by immunoblot Conclusions: Aldosterone and Ang II can increase the expression of CYP11B2 through a crosstalk between GPER-1 and AT1R receptors. In HAC15 cells AT1R and GPER-1 form heterodimers which interact to induce an autonomous aldosterone production in APAs.